THE EDUCATIONAL VALUES THROUGH THE HOLISTIC MATHEMATICS EDUCATION (HME) MODEL BASED ON AMONG SYSTEM IN LOW CLASSES - Rahmatul Hayati; Desri Jumiarti; Wahyu Prima; Dodi Widia Nanda (Universitas Pendidikan Indonesia, 2022)
A good education in low-classes does not only aim to foster an academic aspect, but also establish a non-academic side in order to have good personality and characters. Hence, mathematics is one of the sciences that is appropriate to develop all of these potentials. Some prior research results have delineated that mathematics is not only effective to expand students’ intelligence, but also form learners’ characters. Therefore, this paper presents that the Holistic Mathematics Education (HME) model based on among system is one of the educational values used to develop students’ characters in low-classes.